An Assessment of the Economic Viability of Delivering Solar PV Rooftop as a Service to Strengthen Business Investment in the Residential and Commercial Sectors - Leewiraphan, Chavid; Ketjoy, Nipon; Thanarak, Prapita (International Journal of Energy Economics and Policy, 2024)
The creation of significant power from PV technology has resulted from the growth of the solar PV business and industry and the lowering of PV costs. The electricity market is open broader for PV and other involved device technology. The goal of cumulative capacity drives Thailand’s solar PV investment compass. The learning curve projection shows that the prediction’s learning curve reliability can provide a clearer view for PV investment and policymakers. This paper shows the creation of the opportunity for the solar PV rooftop as a service (RaaS) business model, designed for four customers: residential and commercial, with small, medium, and large scales depending on their electricity consumption. The result reveals that if no grid is allowed, the medium- and large-scale are more likely to be feasible as they show grid parity. With the PV cost reduction trend, all the customers are economically viable in the grid sale allowed. Besides that, the electricity tariff rate from the grid also significantly impacts the PV rooftop investment and customer decision-making.